Furcellaran nanocomposite films: The effect of nanofillers on the structural, thermal, mechanical and antimicrobial properties of biopolymer films - Jamróz, Ewelina; Khachatryan, Gohar; Kopel, Pavel; Juszczak, Lesław; Kawecka, Agnieszka; Krzyściak, Paweł; Kucharek, Mateusz; Bębenek, Zuzanna; Zimowska, Małgorzata (Carbohydrate polymers, 2020)
Graphene oxide (GO) and multi-walled carbon nanotubes (MWCNTs) were added to furcellaran films (FUR). Silver nanoparticles (AgNPs) were prepared by reducing AgNO3 using a FUR matrix as the stabilising agent. The structure and surface morphology of nanocomposite films were obtained using FTIR, SEM and XRD. The molecular weights of furcellaran chains were estimated using HPSEC-MALLS-RI. Characterisation of the films was undertaken to analyse their physical, mechanical and structural properties. SEM analysis revealed that GO, MWCNTs and AgNPs were evenly distributed throughout the FUR surface. FUR + AgNP films showed antimicrobial activity against bacteria and fungi. P. aeruginosa, E. faecalis and S. aureus were the most affected with effective growth inhibition using the disc diffusion method. In the study, the effect of nanofillers on the structural, thermal, mechanical and antimicrobial properties of furcellaran films as potential materials for food packaging is presented.
Keywords: Nanocomposites; Nanotubes, Carbon; algináty; Multi-walled carbon nanotubes; grafit; Biopolymers; biopolymery; Plant Gums; Furcellaran; Nanofillers; antibakteriální látky; Silver; kovové nanočástice; Alginates; Silver nanoparticles; Anti-Bacterial Agents; stříbro; Graphite; Graphene oxide; nanotrubičky uhlíkové; Nanocomposite films; Bacteria; Metal Nanoparticles; rostlinné gumy; nanokompozity